Late-career entrepreneurship, income and quality of life - Kautonen, Teemu; Kibler, Ewald; Minniti, Maria (Journal of Business Venturing, 2017)
Late-career transitions to entrepreneurship are discussed as a promising way to address some of the problematic implications of population aging. By extending employment choice theory to simultaneously account for career stage and for non-monetary rewards from entrepreneurship, we investigate how late-career transitions from organizational employment to entrepreneurship influence the returns from the monetary (income) and non-monetary (quality of life) components of an individual's utility. Using data from the English Longitudinal Study of Ageing, our empirical analysis shows that for late-career individuals, starting a business is positively associated with change in quality of life and negatively associated with change in income.